Perbedaan Kontrol Glikemik Terapi Metformin Dibandingkan Glimepiride pada Pasien Diabetes Melitus Tipe 2 di RSI Jemursari Surabaya pada Tahun 2018 - Rachma Putri Nariswari; Gwenny Ichsan Prabowo; Hermina Novida; Nurina Hasanatuludhhiyah (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Introduction: Type 2 diabetes mellitus is caused by decreased tissue sensitivity to insulin. The prevalence of diabetes in the world has almost doubled since 1980, from 4.7% to 8.5% in adult population. Early diagnosis and treatment aimed at normalizing glycemic control are very important. The objective of this study was to evaluate and compare glycemic control of metformin and glimepiride in monotherapy of type 2 diabetes mellitus patients at Islamic Jemursari Hospital Surabaya. Method: This was a retrospective observational study using secondary data (medical record), include glycemic control (RPG) before and two months after receiving therapy of outpatients’ type 2 diabetes mellitus with metformin or glimepiride therapy in 2018. 96 samples were found that fit the inclusion criteria. The data were analyzed by Mann-Whitney test. Result: Most patients were female, aged 50-69 years old, and dosage of metformin therapy 1500 mg/day or glimepiride therapy 2 mg/day. There was no significant difference (p greater than 0.05) of glycemic control (RPG) of metformin compared to glimepiride therapies in type 2 diabetes mellitus patients at Islamic Jemursari Hospital Surabaya in 2018. Conclusion: Metformin and glimepiride were not significantly different in glycemic control (RPG). There were patients with RPG greater than 200 mg/dl after two months of metformin or glimepiride therapy.